HUBUNGAN PENDIDIKAN KESEHATAN TENTANG PIJAT BAYI TERHADAP PENGETAHUAN IBU DI DESA KEPENUHAN HULU KABUPATEN ROKAN HULU - Eka Yuli Handayani; Sri Wulandari (Fakultas Ilmu Kesehatan, 2021)
Baby massage is a relaxation technique given to infants and toddlers who provide many benefits for children. Baby massage is useful to help the baby's immune system, help train relaxation, make sleep better, and help the regulation of the digestive and respiratory systems. Massage also optimizes the growth of babies. The purpose of the study was to find out the relationship of health education about baby massage to the knowledge of mothers in Kepenuhan Hulu Vllagge. This type of research is a pre experiment with the design of one group pretest posttest. The number of samples is 65 people determined by the total sampling technique. The statistical test used is paired t test. The results showed that respondents' knowledge before being given health education about baby massage on average was 13.52 and after being given health education to 16.23. Based on the results of statistical tests there is an influence of health education about baby massage on the knowledge of the mother with the results of statistical tests obtained a value of p is 0.0001 (p < 0.05). It is expected that with the information and knowledge about baby massage, the mother has the desire and motivation to do a massage to her baby.